Retinal Vascular Caliber as a Biomarker for Diabetes Microvascular Complications - Ikram, M. Kamran; Cheung, Carol Y.; Lorenzi, Mara; Klein, Ronald; Jones, Teresa L.Z.; Wong, Tien Yin (Diabetes care, 2013)
[...]investigators have attempted over the decades to identify early changes in the retinal vessels in diabetes and determine whether they could inform about the development of retinopathy and other complications. [...]the incremental value of a novel biomarker over standard available biomarkers should be assessed not only with standard statistical measures such as the area under the curve (AUC) of the receiver operating characteristic curve or C-statistic, but also with more recently developed measures such as weighted net reclassification index (wNRl) and net benefit (NB) (5).